Pengaruh Materi dan Metode Pelatihan terhadap Kemampuan Kerja Karyawan PD BPR Bantul, Yogyakarta - Suhartini, Yati (AKMENIKA, 2019)
The research was carried out to find the influence of training material and methods of training toward workability. The study was conducted respectively from an employee of PD BPR Bantul Yogyakarta. The population of the research is 61 employees who have attended training. Data were derived from a survey, collected by applying questionnaires, analyzed by using multiple linear regression, and assisted by the application of the SPSS program. Based on the result of data analysis, it was shown that the three independent variables, namely training material (X1), on the job training (X2), and off the job training (X3) influence partially or simultaneously on workability (Y), thus partially or simultaneously supporting the five hypotheses. Those were indicated by the value of the regression coefficient and the significant level of each factor, which are 0.407 and 0.008; 0.312 and 0.036; 0.443 and 0,000, respectively. Likewise, the value of F amounting to 28,483 with the significance level of 0,000, whereas adjusted R2 counting to 0.579. Furthermore, off the job training indicates as the most dominant variable that influences on workability.